Nurse’s Workload, Patient Safety and Quality of Care; A Descriptive Study in Tertiary Care Hospital: Workload and Quality of Care in Nurses - Rahman, Saad Ur; Mehmood, Asif; Naz, Irum; Shaista, .; Ismail, Muhammad; Adeel, Muhammad; Gul, Sana; Islam, Muhammad; Uddin, Minhaj (Pakistan BioMedical Journal, 2024)
The study was conducted on Registered Nurses at Mardan Medical Complex, Mardan Khyber Pakhtunkhwa. Objective: To explore the nurses’ workload, its effect on patient safety and quality of care in Mardan Medical Complex, Mardan. Methods: A descriptive cross-sectional design was selected for the study. A sample size of 107 nurses was calculated through Raosoft software. For this, data collection tools consisted of a Demographic profile, the Maslach Burnout Scale, and the Nurses Report of Quality of Care. The collected data were analyzed through a Statistical Package of Social Sciences (SPSS) version 26.0 and Microsoft Excel. Results: On analysis of 115 structured questionnaire responses, the result disclosed most of the nurses were fed up with working all day long and delivered their maximum effort for their patients with the inappropriate number of staff. They rationalized their hard work with the belief in equality and providing care to humanity. With a high workload, they still feel satisfied and treat their patient apathetically. The nurses showed relatedness of poor quality of care to the high workload and low nurse-patient ratio. Conclusions: The nurses’ workload has a direct effect on the patient’s health. To maintain the quality of care, the nurse-patient ratio needs to be standardized. With an appropriate nurse-patient ratio, the nurses will then not prioritize the major intervention but will comprehensively and holistically care for their patients which will positively affect the quality of patient care.